Influence of various treatments on pre and post germination properties of Callistephus chinensis (L.) Nees cv. Powderpuff (Bangladesh Journal of Botany, 2019)
Seeds of China aster cv. Powderpuff were subjected to two conditioning techniques viz, hydroconditioning and halo-conditioning at different levels of concentrations and subjected time durations, constituting a total of 16 treatment combinations (P1 - P15) along with control (P0). Hydro-priming for 12 hrs and the halo-priming with 2 % KNO3 for 12 hrs significantly improved germination, mean germination time, germination index, germination rate index and growth attributes of China aster cv. Powderpuff. Hydropriming being simple economical and eco/subject friendly and safe is recommended for effective germination and growth of China aster cv. Powderpuff.